Chain Dance Teshkoto – Cultural Identity Marker of Macedonians - Zdravkova-Djeparoska, Sonja (İTÜ TMDK (Istanbul Technical University Turkish Music Conservatory), 2017)
Every nation through the process of building identity chooses symbols that shall identify and represent it. Unlike many examples of taking heraldic symbols, emblems associated with the geographic, political, religious characteristics; Macedonia is a rare case where a dance becomes an identification code. That is Macedonian dance Teshkoto, from the Reka region. Regarding the construction of Teshkoto as an identity marker, we can notice two separate processes. The first one was the emergence and development of components that cre ated and complemented the meaning of the dance. The second phase was the process of acceptance and establishment of this dance form as a national symbol. Its development as a cultural marker can be followed through two periods - the period of the Socialist Re public of Macedonia as a part of SFR Yugoslavia and the period of independence of the Republic of Macedonia. Namely, despite differences in the socio-political context, the trend of promoting and glorifying exact folk dance form - Teshkoto continues. The example of Teshkoto shows the process of inauguration of a consciously chosen identity marker and its acceptance as a national symbol.
Keywords: Macedonia, dance, Teshkoto, identity